Synchronous Online Discussion: Its Contributions to Language Learning - Abdul Ghani, Rozina; Mat Daud, Nuraihan (UKM, 2006)
Computer-mediated communication offers enormous opportunities for teaching English. This paper examines some of the contributions of classroom synchronous online communication towards language learning. Synchronous communication held in three ESL/EFL classrooms in a tertiary institution in Malaysia is studied for this purpose. The focus of the study is on small group discussions. The study shows that the students produced a wide variety of discourse functions in their discussion, participated almost equally amongst themselves and they were also involved in the construction of knowledge. The study also acknowledges the important role played by the teacher and the group leader especially in moderating small group discussions.